Assessing agrifood system growth outcomes in Tajikistan - Khakimov, Parviz; Diao, Xinshen; Goibov, Manuchehr; Ashurov, Timur (International Food Policy Research Institute, 2025)
On March 1, 2023, the Government of Tajikistan adopted a new sectoral program, “Agrifood System and Sustainable Development Program,” for the period up to 2030. The program defined six priorities, namely (1) strengthening institutions, (2) enabling physical infrastructure, (3) creating an agriculture extension system, (4) ensuring food and nutrition security, (5) ensuring food safety and, veterinary and plant protection, and (6) establishing effectively functioning value chains. The Program aims to ensure sustainable development of the sector and enhance its competitiveness through structural and institutional reforms, by boosting sector productivity, creating new jobs, and ensuring food security. To inform the policy by providing empirical evidence, in this brief, first we assess and compare diverse contributions of different agrifood value chains to broad development outcomes, second, we assess the effectiveness of agricultural productivity-led growth across agrifood value chain groups for achieving multiple development outcomes (economic growth, job creation, declining poverty, and improved diets) and inclusive agrifood system transformation in Tajikistan.